Characterization of Intelligent Packaging from Chitosan-Cassava Starch with Butterfly Pea Flower Extract and Gambier Catechin as Freshness Sensor - Rahmadhia, Safinta Nurindra; Septiani, Ifha Nur; Fitriani, Aprilia; Putri, Soraya Kusuma (Trends in Sciences, 2025)
The increasing environmental concerns associated with conventional plastic packaging have accelerated research into biopolymer-based alternatives for sustainable food packaging. Starch and chitosan have emerged as promising biodegradable materials, while the incorporation of bioactive and natural pigments enables the development of intelligent packaging systems. Anthocyanins from butterfly pea flower extract, stabilized through co-pigmentation with gambier catechins, provide pH-sensitive functionality for monitoring food quality and safety. This study contributes to the formulation of intelligent biopolymer films as pH sensors for assessing chicken freshness under varying storage conditions. The production of intelligent film used various concentrations of butterfly pea flower extract and gambier (BPG) (5%, 10% and 15%) incorporated into chitosan-cassava starch solution. The physical properties of the film were observed following the analysis of the color response of the BPG extract and intelligent film. Then, the BPG intelligent film was applied to monitoring chicken breast freshness for 72 h at 7 and 25 °C. The color and pH changes were observed every 24 h. The BPG intelligent film significantly increased film thickness, moisture content, solubility, water vapor transmission rate (WVTR), and water vapor permeability (WVP). The color of the BPG extract and BPG film shifted from purple to green at pH levels between 2 and 11. When applied to chicken breast, the color of the BPG film will change from purple to green due to the decay in the chicken breast which is indicated by an increase in pH. Based on the research results, it can be concluded that BPG extract mixed with the film matrix can act as a freshness indicator in chicken breast stored at cold or room temperature. The color change that occurs is clearly visible (does not fade) due to the co-pigmentation of gambier. HIGHLIGHTS Butterfly pea flower as an anthocyanin source is incorporated into a biopolymer matrix made from chitosan-cassava starch. Anthocyanin from butterfly pea flower extract is a pH-sensitive pigment that will produce color changes. A chitosan-cassava starch film supplemented with butterfly pea flower extract was used to monitor the freshness of chicken breasts. The intelligent film applied to the chicken breasts exhibited color changes during storage, indicating that the samples were deteriorating. GRAPHICAL ABSTRACT